A theoretical model of transition to practice for athletic trainers - Kilbourne, B. F.; Bowman, T. G.; Barrett, J. L.; Mazerolle Singe, S. (Journal of Athletic Training, 2021)
Context: The transition to practice of newly credentialed athletic trainers (ATs) has become an area of focus in the athletic training literature. However, no theoretical model has been developed to describe the phenomenon and drive investigation. Objective: To better understand the lived experience of the transition to practice and develop a theoretical model of transition to practice for ATs. Design: Qualitative study. Setting: Telephone interviews. Patients or Other Participants: Fourteen professional master's athletic training students (7 men, 7 women, age = 25.6 ± 3.7 years, from 9 higher education institutions) in the first year of clinical practice as newly credentialed ATs. Data Collection and Analysis: Participants completed semistructured phone interviews at 3 timepoints over 12 to 15 months. The first interview was conducted just before graduation, the second 4 to 6 months later, and the third at 10 to 12 months. The interviews were transcribed and analyzed using a grounded theory approach. Results: We developed a theoretical model to explain the causal conditions that triggered transition, how the causal conditions were experienced, the coping strategies used to persist through the first year of practice, and the consequences of those strategies. Conclusions: The model provides a framework for new athletic training clinicians, educators, and employers to better understand the transition process in order to help new clinicians respond by accepting or adapting to their environment or their behaviors.